2021
DOI: 10.1503/cjs.010719
|View full text |Cite
|
Sign up to set email alerts
|

A systematic review of global surgery partnerships and a proposed framework for sustainability

Abstract: Background: Building surgical capacity through global surgery partnerships (GSPs) between high and low- and middle-income countries (LMICs) is a rising global health focus. Our aim was to conduct a systematic review to characterize strategies employed by GSPs to build capacity and promote sustainability and to propose a novel reproducible model for sustainability. Methods: We conducted a systematic review according to the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) statement. W… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
25
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(28 citation statements)
references
References 22 publications
1
25
0
Order By: Relevance
“…10 11 Yet, whereas the content of any singular global surgery project has varied, a systematic review of partnerships between North American and LMIC institutions found that over 81% of these projects included a surgical education component. 12 Other partnerships have included help with accreditation bodies, technology acquisition, research capacity, library access and human resource development. 13 Such a focus on surgical education is prudent; it is well known that physicians tend to stay where they train.…”
Section: Open Accessmentioning
confidence: 99%
See 2 more Smart Citations
“…10 11 Yet, whereas the content of any singular global surgery project has varied, a systematic review of partnerships between North American and LMIC institutions found that over 81% of these projects included a surgical education component. 12 Other partnerships have included help with accreditation bodies, technology acquisition, research capacity, library access and human resource development. 13 Such a focus on surgical education is prudent; it is well known that physicians tend to stay where they train.…”
Section: Open Accessmentioning
confidence: 99%
“…Indeed, definitions of such have varied over the years, with one group framing it as ‘the enterprise of providing improved and equitable surgical care to the world’s population, with its core tenets as the issues of need, access and quality’ and another author characterising it far more comprehensively as the ‘area for study, research, practice, and advocacy that places priority on improving health outcomes and achieving health equity for all people worldwide who are affected by surgical conditions or have a need for surgical care’ 10 11. Yet, whereas the content of any singular global surgery project has varied, a systematic review of partnerships between North American and LMIC institutions found that over 81% of these projects included a surgical education component 12. Other partnerships have included help with accreditation bodies, technology acquisition, research capacity, library access and human resource development 13…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is also a key focus of international surgical partnerships. In a systematic review of global surgery partnerships between North American and LMIC institutions, Jedrzejko et al [8] find that 81% of partnerships contain a surgical education or training component.…”
Section: Introductionmentioning
confidence: 99%
“…5 Successful engagements range from short-term missions to long-term partnerships, though always with an emphasis on respectful and meaningful collaboration with the local health system and workforce. 6 These partnerships have led to important gains influencing policy and strategy at national and international levels, which are necessary to promote costeffectiveness and sustainability. 7 Advances in technology have led to a revolution in the approach to surgical capacity building globally.…”
mentioning
confidence: 99%